Thrombophilia and outcome in severe infection and sepsis - Hofstra, Jorrit-Jan; Schouten, Marcel; Levi, Marcel (Seminars in thrombosis and hemostasis, 2007)
Thrombophilia is associated with a prohemostatic state and consequently with an increased tendency to develop thrombosis. In severe infection and sepsis, activation of coagulation frequently occurs, which contributes to the development of multiple organ dysfunction. Hypothetically, patients with thrombophilia may suffer from more severe coagulopathy in the presence of severe infection or sepsis, which may result in a more serious clinical course and an unfavorable outcome. This article reviews experimental and clinical evidence regarding such a relationship, with a particular focus on deficiencies of natural anticoagulant proteins (protein C and antithrombin), the factor V Leiden mutation, and genetic variation in the fibrinolytic system.